2013
DOI: 10.1044/1092-4388(2013/12-0335)
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of Clear Speech: Effect of Instruction

Abstract: Purpose The authors investigated how clear speech instructions influence sentence intelligibility. Method Twelve speakers produced sentences in habitual, clear, hearing impaired, and overenunciate conditions. Stimuli were amplitude normalized and mixed with multitalker babble for orthographic transcription by 40 listeners. The main analysis investigated percentage-correct intelligibility scores as a function of the 4 conditions and speaker sex. Additional analyses included listener response variability, indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Further research is needed to investigate the impact of instruction when using a clear speech training program. Previous studies have reported that different clear speech instructions also vary in the amount of clear speech benefit or intelligibility increase in young healthy adults (Lam & Tjaden, 2013a). It is unknown whether this relationship holds for speakers with PD.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Further research is needed to investigate the impact of instruction when using a clear speech training program. Previous studies have reported that different clear speech instructions also vary in the amount of clear speech benefit or intelligibility increase in young healthy adults (Lam & Tjaden, 2013a). It is unknown whether this relationship holds for speakers with PD.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
“…However, the instructions used to elicit clear speech vary widely across studies. In our previous research with young healthy adult speakers, three variants of clear speech instruction-including "Overenunciate each word," "Speak to someone with a hearing impairment," and "Speak clearly"-differentially affected the magnitude of acoustic adjustments and, in turn, positively correlated to the amount of clear speech intelligibility benefit (Lam & Tjaden, 2013a, 2013bLam, Tjaden, & Wilding, 2012). In the current study, we extend this line of inquiry to speakers with PD and a group of age-and sex-matched controls.…”
mentioning
confidence: 99%
“…Whether certain cues for eliciting clear or loud speech serve to maximize intelligibility is worthy of study in the future, perhaps especially in light of research suggesting that the cue for stimulating an increased vocal intensity affects the nature of the speech production adjustments in PD (Darling & Huber, 2011). Clear speech instructions also have been shown to impact the magnitude of acoustic adjustments made by neurologically healthy talkers (Lam et al, 2012), as well as the magnitude of the improvement in intelligibility (Lam & Tjaden, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…One observation that seems to be common among studies of intelligibility involving both children and adults across disorder populations is that there is considerable variability in the performance of different listeners who hear the same speaker (interlistener variability; see Hustad & Cahill, 2003;Hustad et al, 2012;Lam & Tjaden, 2013;Montag, AuBuchon, Pisoni, & Kronenberger, 2014;Pennington et al, 2013). In fact, studies report standard deviations within a given speaker across listeners of up to 17% for individuals with the most severe dysarthria and slightly lower for those speakers with less severe dysarthria (Hustad & Cahill, 2003).…”
Section: Listener Variability In Intelligibility Measurementmentioning
confidence: 99%